[OA009] Motion inclusive variations in bladder dose surface maps during the course of high-precision radiotherapy for prostate cancer. (August 2018) - Clark, Hal; Casares-Magaz, Oscar; Pettersson, Niclas; Muren, Ludvig; Hopper, Austin; Knopp, Rick; Einck, John; Moiseenko, Vitali
Abstract : Purpose: Modern radiotherapy (RT) protocols for prostate cancer often involve the use of narrow margins and image-based monitoring of rectum/bladder fill status. These protocols have allowed safe prostate dose escalation, maintaining acceptable levels for organs at risk (bladder and rectum). However, daily cone-beam CT (CBCT) image-guided RT has demonstrated considerable bladder volume variation throughout treatment, which suggests dose delivered may vary. By using CBCT-based parametrized 2D dose surface maps (DSM) of the inferior bladder, this study aims to evaluate bladder volume impact on bladder DSMs during high-precision RT for prostate cancer. Methods: Seven prostate cancer patients treated using daily CBCT-based image-guided VMAT/IMRT were included in this study (81.0 Gy prescription dose). Planning CT and RT delivery adhered to a full bladder/empty rectum protocol, where daily CBCTs were used for patient realignment and to assess bladder/rectum filling status. Fourteen CBCTs per patient were rigidly registered to the planning CT using recorded treatment shifts, and the bladder was manually contoured on each CBCT. Contours were validated by the responsible radiation oncologist. For the planning CT and each CBCT, bladder wall dose was digitally projected onto 1024x1024 DSMs using orthographic ray-traced surface dose sampling. Bladder wall volumetric meshes were generated from contours using restricted Delaunay triangulation. Surface dose was sampled at ray-wall intersections, sub-pixel sampling was used to improve image quality, and rays were oriented parallel to the prostate-bladder center-of-mass connecting line. DSM dose distributions were compared between planned and delivered. Correlation with bladder volume variations was evaluated. Results: Bladder volumes varied considerably during RT (15–42%), with slightly larger volumes at planning compared to treatment (p = 0.16). Differences at the central part of the DSM ranged between 1% and 7%. Overall, delivered doses were lower at the central part of the DSM compared to planned (range: −5.4 to 0.9 Gy). Plan-vs-delivery mean dose differences were slightly correlated with bladder volume differences (Rs = 0.55, p = 0.3). Conclusions: No significant variations were observed in delivered doses at the interior part of the bladder although considerable bladder volume changes occurred during the RT course. The generally smaller treatment bladder volume possibly explains lower dose delivered to the inferior bladder sector.